Application of X-ray fluorescence in investigations of Bohemian historical manuscripts - Čechák, Tomáš; Trojek, Tomáš; Musílek, Ladislav; Paulusová, Hana (Applied radiation and isotopes, 2009)
In this work we present the application of X-ray fluorescence analysis (XRFA) in an investigation of the Land Register and the Register of the Court of the Kingdom of Bohemia and the manuscript of the Homiliary of the Opatovice Monastery from the 12th century. Radionuclide sources emitting radiation at an appropriate energy level and an X-ray tube were used to excite the characteristic radiation. A spectrometric Si(Li) detector and a Si-PIN detector with Peltier cooling were used to detect the excited characteristic radiation. Several types of pigments were identified and compositions of inks used within almost 5 centuries in the offices at the Prague Castle were determined.
Keywords: Coloring Agents; Česká republika; History, Medieval; Czech Republic; X-Ray Diffraction; dějiny středověku; Manuscripts as Topic; difrakce rentgenového záření; barvicí látky; rukopisy jako téma